The Effect of Taxes on Labor Supply in the Underground Economy - Lemieux, Thomas; Fortin, Bernard; Fréchette, Pierre (American Economic Review, 1994)
This paper uses micro data from a randomized survey carried out in the Metropolitan area of Quebec City, Canada, to analyze the decision to evade taxes and work in the "underground" economy. The results indicate that taxes distort labor-market activities away from the regular sector to the underground sector, but the distortion is small for the average worker. The distortion is large, however, for particular groups of the population such as welfare claimants.